Fast Clinical Response of Bimekizumab in Nail Psoriasis: A Retrospective Multicenter 36-Week Real-Life Study - Elena Campione; Fabio Artosi; Ruslana Gaeta Shumak; Alessandro Giunta; Giuseppe Argenziano; Chiara Assorgi; Anna Balato; Nicoletta Bernardini; Alexandra Maria Giovanna Brunasso; Martina Burlando; Giacomo Caldarola; Anna Campanati; et al. (MDPI AG, 2024)
(1) Background/Objectives: Nail psoriasis (NP) is a chronic and difficult-to-treat disease, which causes significant social stigma and impairs the patients' quality of life. Moreover, nail psoriasis is a true therapeutic challenge for clinicians. The presence of nail psoriasis can be part of a severe form of psoriasis and can have predictive value for the development of psoriatic arthritis. Our real-world-evidence multicenter study aims to evaluate the efficacy of bimekizumab in nail psoriasis. (2) Methods: A retrospective analysis of a multicenter observational study included 834 patients affected by moderate-to-severe psoriasis, in 33 Dermatologic Units in Italy, treated with bimekizumab from December 2022 to September 2023. Clinimetric assessments were based on Psoriasis Area and Severity Index (PASI), Dermatology Life Quality Index (DLQI), and Physician's Global Assessment of Fingernail Psoriasis (PGA-F) for the severity of nail psoriasis at 0, 12, 24, and 36 weeks. (3) Results: Psoriatic nail involvement was present in 27.95% of patients. The percentage of patients who achieved a complete clearance of NP in terms of PGA-F 0 was 31.7%, 57%, and 88.5% at week 4, 16, and 36, respectively. PASI 100 was achieved by 32.03% of patients at week 4, by 61.8% at week 16, and by 78.92% of patients at week 36. The mean baseline PASI was 16.24. The mean DLQI values for the entire group of patients at baseline, at week 4, at week 16, and at week 36 were 14.62, 3.02, 0.83, and 0.5, respectively. (4) Conclusions: Therapies that promote the healing of both the skin and nails in a short time can also ensure a lower risk of subsequently developing arthritis which is disabling over time. Bimekizumab proved to be particularly effective to treat NP, with a fast response in terms of complete clearance, with over 88.5% of patients free from NP after 36 weeks. The findings of our real-world study showed that patients with moderate-to-severe PsO and concomitant NP had significantly faster and more substantial improvements in NP up to 36 weeks with respect to previous research findings. Considering the rapid healing of the nail, the dual inhibition of IL17 A and F might have a great value in re-establishing the dysregulation of keratin 17 at the nail level.